2016
DOI: 10.3389/fimmu.2016.00459
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-Prostaglandin J2 Modifies Components of the Proteasome and Inhibits Inflammatory Responses in Human Endothelial Cells

Abstract: 15-Deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) is an electrophilic lipid mediator derived from PGD2 with potent anti-inflammatory effects. These are likely to be due to the covalent modification of cellular proteins, via a reactive α,β-unsaturated carbonyl group in its cyclopentenone ring. This study was carried out to identify novel cellular target(s) for covalent modification by 15d-PGJ2 and to investigate the anti-inflammatory effects of the prostaglandin on endothelial cells (EC). The data presented here show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 52 publications
0
14
0
Order By: Relevance
“…A complex interplay can also occur with the protein degradation machinery. Certain oxidative insults or other types of stress can lead to the degradation of vimentin and GFAP by activating proteases [ 179 ], although some ubiquitin ligases and subunits of the proteasome can be inhibited by lipoxidation [ 180 ], which, as stated above, would result in accumulation of damaged proteins.…”
Section: Interplay Between Ptms In Type III Ifsmentioning
confidence: 99%
“…A complex interplay can also occur with the protein degradation machinery. Certain oxidative insults or other types of stress can lead to the degradation of vimentin and GFAP by activating proteases [ 179 ], although some ubiquitin ligases and subunits of the proteasome can be inhibited by lipoxidation [ 180 ], which, as stated above, would result in accumulation of damaged proteins.…”
Section: Interplay Between Ptms In Type III Ifsmentioning
confidence: 99%
“…Therefore, the same PG can have the opposite effect depending on the activated signaling pathways [107]. Most PGs have a proinflammatory effect (for example, PGE2 and PGD2), but some of them, cyclopentenone PG (PGA2 and 15d-PGJ2) in particular, are characterized by anti-inflammatory and antioxidant properties and participate in the regulation of glucose metabolism [92].…”
Section: Natural and Synthetic Ligands Of Ppars In Asthma Therapymentioning
confidence: 99%
“…The α,β-unsaturated carbonyl group located in the cyclopentenone ring can form a covalent bond with the thiol group of cysteine residues. Treatment of human aortic endothelial cells with 15d-PGJ 2 resulted in 15d-PGJ 2 -modified 19S-subunits, e.g., RPN1, RPN2, RPN3, and RPN6, while 20S-subunits were unmodified (Marcone, 2016). Further examination showed that the ChT-L activity of the proteasome was inhibited and ubiquitin-conjugated proteins were accumulated.…”
Section: Proteasome Modulation By Post-translational Modificationsmentioning
confidence: 99%
“…15d-PGJ 2 has anti-inflammatory actions, for instance by inhibiting nuclear factor-κB (NF-κB) activation (Surh et al, 2011). A possible mechanism for 15d-PGJ 2 to suppress the NF-κB pathway is by modifying and inhibiting the proteasome, which regulates the processing of NF-κB inhibitors (Marcone, 2016). 15d-PGJ 2 treatment reduced the adhesion and migration of monocytes toward TNF-α-exposed endothelial cells, a key process in vascular inflammation, and similar effects were observed upon proteasome inhibition.…”
Section: Proteasome Modulation By Post-translational Modificationsmentioning
confidence: 99%